Vitamin D status and determinants of deficiency in non-supplemented athletes during the winter months in Tunisia - A Sghaier-Ayadi; M Feki; I Bezrati-Ben Ayed; O Abene; MK Ben Fredj; K Kaabachi; A Chaouachi (Termedia Publishing House, 2015)
Recent reports suggest that hypovitaminosis D in athletes is as common as in the general population. This study was devised to examine vitamin D status and determinants of deficiency in athletes living in a sunny country (Tunisia). One hundred and fifty national elite athletes, training outdoors (n=83) or indoors (n=67), were enrolled from January to February 2012. Plasma 25-hydroxyvitamin D was measured by radioimmunoassay. Concentrations were between 50 and 75 nmol · l -1 in 21.3% of participants, between 25 and 50 nmol · l -1 in 55.3% of participants and <25 nmol · l -1 in 14.7% of participants. The concentrations were significantly lower in indoor athletes than outdoor athletes (36.2±19.0 nmol · l -1 vs. 49.1±19.2 nmol · l -1 ; p<0.001). In multivariate analysis, vitamin D deficiency (25-hydroxyvitamin D <50 nmol · l -1 ) was associated with indoor sports [multi-adjusted odds ratio (95% confidence interval), 5.03 (1.64-15.4); p=0.005], female gender [3.72 (1.44-9.65); p=0.007] and age < 18 years [2.40 (1.01-5.85); p=0.05]. Athletes living in sun-rich environments are exposed to a high risk of vitamin D inadequacy. Given the importance of vitamin D in health and athletic ability, targeting sufficient levels of plasma 25-hydroxyvitamin D in athletes is well justified.